A V-Band Doherty Power Amplifier Based on Voltage Combination and Balance Compensation Marchand Balun - Dong Chen; Chenxi Zhao; Zhengdong Jiang; Kam Man Shum; Quan Xue; Kai Kang (IEEE Access)
This paper presents a $V$ -band Doherty power amplifier (PA) which is implemented in a standard 65-nm CMOS technology. The voltage combination technique is used to realize the millimeter-wave Doherty PA without the $λ $ /4 transmission lines. A Marchand balun with balance compensation is designed to combine the output power with reduced power loss. Moreover, a nonlinear driver is used to drive the peaking amplifier to enhance the output power and the turn-on speed of it. The power-added efficiency (PAE) of this PA at the 6-dB power back-off point is 8.7% and the peak PAE reaches 16.8%. The small signal power gain is 18 dB, and the maximum output power is 14.9 dBm. The core circuit only costs 0.195 mm2 chip area as no $λ $ /4 transmission lines.